The powers that be - Halberstam, David (Knopf, 1979)
The book provided manna for political, history, political science and journalism junkies and groupies. It bared the warts -- biases, politically partisan maneuverings, egos, dollars-and-cents motivations, personality clashes, society maneuvers, internal political wars, insecurities, chauvinistic behaviors and restricted realities of the news organizations as seen through the people who owned and ran them